An embodied culture of optimism and struggle: the Sungura music of Tongai Moyo - Tembo, Charles (2016)
This paper is lyrical and philosophical examination on hope and optimistic struggle in the sungura music of Tongai Moyo (1968-2011), a Zimbabwean singer-song writer and musician (guitarist) who produced 14 albums in a career span ning over two decades and thus demonstrated the indispensability of optimistic thriving and victory-centered African consciousness. The argument maintained in the article is that a trajectory of thought that is marked by the necessity of possibility and purposeful human agency is discernible in the music of Tongai Moyo. It is emphasized that Tongai Moyo’s vision as embedded and reflected in his music is rewarding for the people of Africa, and around the world. It is further argued that Tongai Moyo takes sungura music to greater heights because his art celebrates victorious thought, while castigating pessimism as impoverishing. Last, the article contends that Tongai Moyo was an Afrocentric musician who breaks the seemingly developing trend in sungura music circles where utter pessimism and victimhood are projected as the only condition of life.